Mo. Rev. Stat 224, ch. 24, art. 2, § 1276 (1879) - (:unkn) unknown (My University, 1879)
Hereafter it shall be unlawful for any person in this state, except he be a sheriff or other officer in the discharge of official duty, to discharge or fire off any gun, pistol or fire arms of any description, in the immediate vicinity of any court house, church or building used for school or college purposes.§
Keywords: DISCHARGE